FTTX Analysis and Applications - Akgun, Tahir; Unverdi, N. Ozlem (IEEE, 2016)
In this study FTTX (Fiber To The X) technology is examined, and data transmission with FTTH (Fiber To The Home) and FTTB (Fiber To The Building) structures are assessed with OptiSystem 14.0 simulation program. It is observed that the quality of the transmitted data improves with the amplifier used. House and building systems which have ONU (Optical Network Unit) architecture are analysed, and FTTH and FTTB structures are compared in terms of quality factors by performing their spectral analysis. It is found that the data transmitted by FTTH architecture is of higher quality than that of FTTB.
Keywords: Communication technologies; optical communications; FTTX; FTTH; FTTB; ONU; quality factor; Engineering